Load Leveling and Voltage Control of Permanent Magnet Synchronous Generator-Based DG Set for Standalone Supply System - Singh, Bhim; Niwas, Ram; Dube, Sunil Kumar (IEEE transactions on industrial informatics, 2014)
This paper deals with the voltage control and load leveling of permanent magnet synchronous generator (PMSG)-based diesel generator (DG) set for standalone supply system. The proposed system is composed of a PMSG and a prototype of diesel engine (DE), along with the distribution static compensator (DSTATCOM) and battery energy storage system (BESS). The DSTATCOM along with BESS is used for loads leveling and voltage control. It also provides balancing of loads, elimination of harmonics, and compensation of reactive power. The battery on dc link of voltage source converter (VSC) of DSTATCOM is used to supply the active power when the load is more than PMSG rating, and it stores the energy during light load periods. The PMSG is always loaded with an optimum load of 80%-100% of its rating. An optimum loading of DG set helps in improving the fuel efficiency of the DE and also helps in load leveling. The reference source currents are estimated using a hyperbolic tangent function-based least mean square (LMS) algorithm. This control algorithm has reduced computation and provides fast convergence rate to eliminate the effect of noise as compared with other LMS algorithms based on adaptive filtering. The voltage control, load compensation, and fuel efficiency improvement in PMSG-based DG set using BESS and DSTATCOM controlled by hyperbolic tangent function-based LMS algorithm are the main contributions of this paper.